Genome-wide DNA methylation pattern in whole blood of patients with Hashimoto thyroiditis - Zhou, Zheng; Liu, Jinjin; Chen, Yun; Ren, Bingxuan; Wan, Siyuan; Chen, Yao; He, Yanhong; Wei, Qiuyang; Gao, Haiyan; Liu, Lixiang; Shen, Hongmei (Frontiers in Endocrinology, 2023)
Background: Hashimoto thyroiditis (HT), a prevalent autoimmune disorder, is not yet thoroughly understood, especially when it comes to the influence of epigenetics in its pathogenesis. The primary goal of this research was to probe the DNAm profile across the genome in the whole blood derived from patients suffering from HT.Method: Using the Illumina 850K BeadChip, we conducted a genome-wide DNAm assessment on 10 matched pairs of HT sufferers and healthy individuals. Genes with differential methylation (DMGs) were identified and underwent functional annotation via the databases of Gene Ontology and Kyoto Encyclopedia of Genes and Genomes. The transcriptional significance of potential epigenetic biomarker genes was corroborated through qRT-PCR.The DNAm profiling across the genome indicated an overall reduction in methylation in HT subjects in comparison with their healthy counterparts. We detected 283 DMPs (adjusted P < 0.05 and |Δβ| > 0.1), among which 152 exhibited hypomethylation and 131 demonstrated hypermethylation. Further analysis exposed a noteworthy concentration of hypermethylated DMPs in the 3´UTR, North Shore, and CpG islands, while there was a significant decrease in the Open Sea (all P < 0.001). The 283 DMPs were broadly distributed from chromosome 1 to 22, with chromosome 6 harboring the most DMPs (n = 51) and chromosome 12 carrying the most DMGs (n = 15). The SLFN12 gene, which presented with extreme hypomethylation in its promoter DMPs among HT patients, was identified as the epigenetic marker gene. Consequently, the SLFN12 mRNA expression was markedly upregulated in HT, displaying a negative relationship with its methylation levels. The area under curve (AUC) value for the SLFN12 gene among HT patients was 0.85 (sensitivity: 0.7, specificity: 0.7), a significant difference compared with healthy controls. The methylation levels of all DMPs in SLFN12 gene were negatively correlated with TSH and one CpG site (cg24470734) was positively assocciated with FT4.with HT, which permits clear differentiation between HT subjects and normal controls through an epigenetic lens. The SLFN12 gene plays a pivotal role in the onset of HT, suggesting that the methylation status of this gene could serve as a potential epigenetic indicator for HT.